Relationships between presence, satisfaction, and persistence in higher education online courses: Assessing the moderating effects of gender, age, and online experience using PLS-MGA - Jonathan Paris, Sawsen Lakhal, Joséphine Mukamurera (Educational Technology & Society)
The extensive adoption of online education by universities worldwide was further propelled by the coronavirus disease pandemic (COVID-19), giving rise to a key challenge: high dropout rates. Previous studies based on the Community of Inquiry (CoI) framework have examined the effects of social presence (SP), cognitive presence (CP), and teaching presence (TP) on student satisfaction and persistence in higher education. The aim of this quantitative study was to investigate the moderating effects of gender, age, and online course experience on these relationships. A total of 762 online questionnaires were completed by students enrolled in two French-language universities in Canada. Data were analyzed using partial least squares structural equation modelling (PLS-SEM) and partial least squares multigroup analysis (PLS-MGA). Results revealed that gender, age, and online course experience moderate the relationships between TP, satisfaction, and persistence, and that TP is a significant component of online courses when satisfaction and persistence are considered.